TAILORING TREATMENT TO THE INDIVIDUAL: A CRITICAL EXAMINATION OF PRECISION MEDICINE AND PERSONALIZED HEALTHCARE THROUGH THE LENS OF GENETICS, LIFESTYLE, AND ENVIRONMENTAL FACTORS - Ibrahim YahyaAlmakrami, TurkiHassan Al Omorat, Meshal Mohammed GhannamShreaf, Shaker Abdullah Salem Al-Yami, Kharsan Ali Alyami, Mohammed Turki H Al harth, AshrufiMohammed ZmalanAlwaaalah (Chelonian Research Foundation, 2023)
This critical review delves into the transformative potential of precision medicine and personalized healthcare, emphasizing the bespoke tailoring of medical treatments to individual patients. By integrating genetic information with comprehensive lifestyle and environmental data, this innovative approach promises to significantly enhance treatment efficacy and patient outcomes. The review explores the scientific foundations underpinning personalized healthcare, including the pivotal role of genetic markers in disease prediction and the consideration of lifestyle and environmental factors in devising treatment plans. It also addresses the cutting-edge technological advancements driving this medical paradigm, from genomic sequencing to artificial intelligence and wearable technology. Despite the promising benefits, the review critically examines the ethical, legal, and social implications arising from personalized medicine, such as privacy concerns, data security, and equitable access to tailored treatments. The challenges and future directions for integrating precision medicine into mainstream healthcare are also discussed, highlighting the need for collaborative efforts and regulatory frameworks to navigate the complex landscape of personalized healthcare. Keywords: Precision Medicine, Personalized Healthcare, Genetic Markers, Lifestyle Factors, Environmental Influences, Technological Advancements, Ethical Challenges, Treatment Efficacy, Data Security, Equitable Access.